EFFECT OF CALCINATION TEMPERATURE ON THE SYNTHESIS OF TiO₂-SiO₂ COMPOSITES AND THEIR PHENOL DEGRADATION PERFORMANCE - relv (HUIT Journal of Science, 2025)
This study investigates the effect of calcination temperature on the synthesis of TiO₂- SiO₂ composites and evaluates their efficiency in degrading phenol from aqueous solutions. The TiO2-SiO2 composite was prepared via a simple sol-gel method, using titanium n-butoxide and tetraethyl orthosilicate as the precursor. To assess the influence of thermal treatment on the microstructural and optical characteristics, the nanopowder was calcinated at temperatures of 400, 450, 500, 550, and 600 °C. The samples were analyzed using various techniques, such as X-ray diffraction (XRD), UV-Vis Diffuse Reflectance Spectra (DRS), and nitrogen adsorption-desorption isotherms (BET). The XRD patterns verify the formation of TiO2 in the anatase phase, with an increase in crystallinity observed as the calcination temperature rises. The photocatalytic performance for phenol degradation was assessed in a batch reactor under simulated natural light, using a 26 W compact lamp. The synthesized TiO2-SiO2 composite (with a Ti/Si molar ratio of 95/5) exhibited the highest photocatalytic activity for phenol degradation, achieving a phenol degradation yield of 91.5% after 4 h of natural light irradiation. This result was obtained under calcination at 500 °C for 2 h.